2019
DOI: 10.1038/s41598-019-48104-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of pHLIP-mediated CEACAM6 Gene Silencing in Lung Adenocarcinoma

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) plays an important role in lung cancer progression. Here, we examined the therapeutic efficacy of CEACAM6 gene silencing using an siRNA delivery platform targeting the acidic tumour microenvironment in a lung adenocarcinoma xenograft mouse model. An siRNA delivery vector was constructed by tethering the peptide nucleic acid form of an siRNA targeting CEACAM6 (siCEACAM6) to a peptide with a low pH-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Furthermore, CEACAM6 expression is significantly upregulated in LUAD in TCGA database, and CEACAM6 mRNA overexpression is associated with poor overall survival as previously reported. 7 Previous studies have also demonstrated that CEACAM6 overexpression in gastric cancer (GC) cells increased apoptotic resistance to 5-FU, 15 while gene silencing of CEACAM6 in pancreatic ductal adenocarcinoma BxPC3 cells resulted in improved sensitivity to gemcitabine through modulation of AKT activity in a Src-dependent manner. 16 However, how CEACAM6 is associated with drug resistance of cancer cells has not yet been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CEACAM6 expression is significantly upregulated in LUAD in TCGA database, and CEACAM6 mRNA overexpression is associated with poor overall survival as previously reported. 7 Previous studies have also demonstrated that CEACAM6 overexpression in gastric cancer (GC) cells increased apoptotic resistance to 5-FU, 15 while gene silencing of CEACAM6 in pancreatic ductal adenocarcinoma BxPC3 cells resulted in improved sensitivity to gemcitabine through modulation of AKT activity in a Src-dependent manner. 16 However, how CEACAM6 is associated with drug resistance of cancer cells has not yet been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have demonstrated the therapeutic potential of pHLIP-mediated CEACAM6 gene silencing or anti-CEACAM6 monoclonal antibody in LUAD. 6,7 However, the role of CEACAM6 in DDP resistance has not been investigated. In our previous studies, we found that CEACAM6 was significantly upregulated in the DDP-resistant A549/DDP cell line compared to parental A549 LUAD cell line through RNA sequencing (data not shown).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of CEACAM6 is also closely related to tumor progression, recurrence, and prognosis. 16,17 Mutation of the MYC gene is very high in MM 18 and its high expression is also related to the invasiveness of breast cancer. In an experimental study performed on mice, the mutation of threonine 58, which encodes the MYC protein, to alanine was linked to the development of breast cancer and the mutation of serine 62 to alanine was found to reduce the incidence of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers are very important in molecular imaging diagnosis. CEACAM6 is one of the members of the CAMCAMs family, is mainly expressed on the cell membrane, and is over expressed in various solid tumors (28)(29)(30). It was also reported that CEACAM6 expression was higher in pancreatic cancer with low differentiation than in medium differentiation, similarly, it was found that CEACAM6 expression was higher in tumor tissues than in adjacent normal tissues in colon cancer (31).…”
Section: The Ceacam6 -Mab-irdye800cw Can Track the Tumor As Well As Metastases In Vivomentioning
confidence: 94%